Impact of comorbidity on survival in peripheral T‐cell lymphomas: A Swedish Lymphoma Registry study. Issue 1 (5th May 2017) - Ellin, Fredrik; Jerkeman, Mats; Törnqvist, Jenny; Brudin, Lars; Relander, Thomas
Abstract: Comorbidity impacts survival in B‐cell lymphoma patients, but the influence in peripheral T‐cell lymphomas (PTCLs) has been little studied. To investigate the impact of comorbidity on outcome in PTCL, we identified adult patients with newly diagnosed PTCL from 2000 to 2009 in the Swedish Lymphoma Registry. Data on comorbidity at diagnosis were retrospectively collected according to the Charlson Comorbidity Index (CCI). Comorbid conditions were present in 263 out of 694 (38%) patients. A CCI score of ≥2 was associated with inferior overall survival (OS) (hazard ratio [HR] 1.63, P  < .001) and progression‐free survival (HR 1.54, P  < .001) in multivariate analysis. In patients undergoing front‐line autologous stem cell transplantation (auto SCT), CCI >0 was associated with inferior OS (HR 2.40, P  = .013). Chemotherapy regimens were classified as curative or low‐intensity treatments. Among patients aged ≥75 years (n = 214), low‐intensity and curative treatment groups had similar OS (HR 0.8, P  = .6), also when adjusted for CCI. In summary, our results demonstrate CCI to be independently associated with survival in PTCLs. Even limited comorbidity impacted survival after front‐line auto SCT, which needs to be considered in treatment decisions. Intensive anthracycline‐based chemotherapy in elderly PTCL patients might be of limited benefit.